Evaluation of atezolizumab immunogenicity: Efficacy and safety (Part 2). Issue 1 (28th September 2021) - Peters, Solange; Galle, Peter R.; Bernaards, Coen A.; Ballinger, Marcus; Bruno, René; Quarmby, Valerie; Ruppel, Jane; Vilimovskij, Alexandr; Wu, Benjamin; Sternheim, Nitzan; Reck, Martin
Abstract: Antibody therapeutics can be associated with unwanted immune responses resulting in the development of anti‐drug antibodies (ADA). Optimal methods to evaluate the potential effects of ADA on clinical outcomes in oncology are not well established. In this study, we assessed efficacy and safety, based on ADA status, in patients from over 10 clinical trials that evaluated the immune checkpoint inhibitor atezolizumab as a single agent or as combination therapy for several types of advanced cancers. ADA can only be observed post randomization, and imbalances in baseline prognostic factors can confound the interpretation of ADA impact. We applied methodology to account for the confounding effects of baseline clinical characteristics and survivorship bias on efficacy. Adjusted meta‐analyses revealed that despite numerical differences in overall survival and progression‐free survival between ADA‐positive and ADA‐negative patients from some studies, ADA‐positive patients from studies with an overall treatment effect derived benefit from atezolizumab, compared with their adjusted controls. Based on large, pooled populations from atezolizumab monotherapy or combination studies, unadjusted descriptive analyses did not identify a clear relationship between ADA status and frequency or severity of adverse events. Data also suggested that any ADA impact is not driven by neutralizing activity. Collectively, this exploratory analysis suggests that the potential for ADA development should not impact treatment decisions with atezolizumab.